Characterization of the complete mitochondrial genome of the Huanhu Yak (Bos Grunniens) - Xiaoyun Wu; Xuelan Zhou; Xuezhi Ding; Chunian Liang; Xian Guo; Min Chu; Hongbo Wang; Jie Pei; Pengjia Bao; Ping Yan (Mitochondrial DNA. Part B. Resources, 2019)
Huanhu yak is a native yak species of China. In the present study, we reported the complete mitochondrial DNA sequence of the Huanhu yak. The complete mitochondrial genome is a circular molecule with 16,323 bp length which consisted of 13 protein-coding genes, 22 tRNA genes, 2 ribosomal RNA genes, and a non-coding control region (D-loop region). The overall nucleotide composition is 33.71% A, 27.26% T, 25.82% C, and 13.21% G, respectively. The phylogenetic analysis showed that the genetic relationship of Huanhu yak is closer to Pali yak.